(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In this work we examine the production of historiography which has been realized on three distinguished personages of the south of Mexico (present state of Guerrero) personages who participated military and politically in the independence and republican processes. Not only the historical work that describes them is quantified, but there is also a valuation of its reaches and their real contribution. It is presented the imbalance of the production as far as amount and condition, trying for identifying the intellectual yearnings that originated it. The article defines that the thickness of this production maintains the same methodological and appreciative support.